Contribution of the Systemic Approach to OH&S Promotion - Fourar, Youcef Oussama; Benhassine, Wissal; Saadi, Saadia; Djebabra, Mébarek (First International Conference on Materials, Environment, Mechanical and Industrial Systems ICMEMIS’19, 2019)
Faced with different representation models of a work situation whose centers of interest vary from one model to another, guides have been developed to try and analyze occupational risks in their entirety. However, the development of these guides poses a double problem: the completeness of this analysis and the order attributed to the analyzed occupational risks. This article aims to solve this problem through a systemic approach that allows to develop a hierarchical model of occupational risks invariants. Its exploitation allows to carry out an exhaustive analysis of occupational risks and consequently the elaboration of a long-term strategy of prevention.